Diabetes and Change in Bone Mineral Density at the Hip, Calcaneus, Spine, and Radius in Older Women - Schwartz, Ann V.; Ewing, Susan K.; Porzig, Anne M.; McCulloch, Charles E.; Resnick, Helaine E.; Hillier, Teresa A.; Ensrud, Kristine E.; Black, Dennis M.; Nevitt, Michael C.; Cummings, Steven R.; Sellmeyer, Deborah E. (Frontiers in Endocrinology, 2013)
Older women with type 2 diabetes mellitus (DM) have higher bone mineral density (BMD) but also have higher rates of fracture compared to those without DM. Limited evidence suggests that DM may also be associated with more rapid bone loss. To determine if bone loss rates differ by DM status in older women, we analyzed BMD data in the Study of Osteoporotic Fractures (SOF) between 1986 and 1998. SOF participants were women >65 years at baseline who were recruited from four regions in the U.S. DM was ascertained by self-report. BMD was measured with dual x-ray absorptiometry (DXA) at baseline and at least one follow-up visit at the hip (N=6624) and calcaneus (N=6700) and, on a subset of women, at the spine (N=396) and distal radius (N=306). Annualized percent change in BMD was compared by DM status, using random effects models. Of 6,867 women with at least one follow-up DXA scan, 409 had DM at baseline. Mean age was 70.8 (SD 4.7) years. Baseline BMD was higher in women with DM at all measured sites. In models adjusted for age and clinic, women with prevalent DM lost bone more rapidly than those without DM at the femoral neck (-0.96% vs. -0.59% per year, p < 0.001), total hip (-0.98% vs. -0.70% per year, p<0.001), calcaneus (-1.64% vs. -1.40% per year, p=0.005), and spine (-0.33% vs. +0.33% per year, p=0.033), but not at the distal radius (-0.97% vs. -0.90% per year, p=0.91). These findings suggest that despite higher baseline BMD, older women with DM experience more rapid bone loss than those without DM at the hip, spine and calcaneus, but not the radius. Higher rates of bone loss may partially explain higher fracture rates in older women with DM.